Decision-making traits and states as determinants of risky choices - Manja Gärtner; Gustav Tinghög; Daniel Västfjäll (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
We test the effects of dual processing differences in both individual traits and decision states on risk taking. In an experiment with a large representative sample (N = 1,832), we vary whether risky choices are induced to be based on either emotion or reason, while simultaneously measuring individual decision-making traits. Our results show that decision-making traits are strong and robust determinants of risk taking: a more intuitive trait is associated with more risk taking, while a more deliberative trait is associated with less risk taking. Experimentally induced states, on the other hand, have no effect on risk taking. A test of state-trait interactions shows that the association between an intuitive trait and risk taking becomes weaker in the emotion-inducing state and in the loss domain. In contrast, the association between a deliberative trait and risk taking is stable across states. These findings highlight the importance of considering state-trait interactions when using dual processing theories to predict individual differences in risk taking.
Keywords: C91; D81; D91; 330; risk preferences; intuition; emotion; reason; experiment